ORIGO: A mission concept to challenge planetesimal formation theories - Marschall, Raphael; Thomas, Nicolas; Ulamec, Stephan; Hviid, Stubbe; Mottola, Stefano; Vincent, Jean-Baptiste; Ferri, Francesca; Herique, Alain; Plettemeier, Dirk; Kereszturi, Ákos; Lavagna, Michèle R.; Prinetto, Jacopo; et al. (Frontiers in Space Technologies, 2023)
Comets are generally considered among the most pristine objects in our Solar System. There have thus been significant efforts to understand these bodies. During the past decades, we have seen significant progress in our theoretical understanding of planetesimal/cometesimals (the precursors of comets) formation. Recent space missions -- such as ESA's Rosetta mission to comet 67P/Churyumov-Gerasimenko -- have provided observations claimed by proponents of different comet formation theories to validate their scenarios. Yet, no single formation paradigm could be definitively proven. Given the importance of understanding how the first bodies in our Solar System formed, we propose a dedicated mission to address this issue. ORIGO will deliver a lander to the surface of a cometary nucleus where it will characterise the first five meters of the subsurface. With remote sensing instruments and the deployment of payload into a borehole, we will be able to study the physico-chemical structure of ancient, unmodified material. The mission has been designed to fit into the ESA M-class mission budget.